IMPROVING ECONOMIC MECHANISMS FOR EFFICIENT RESOURCE UTILIZATION IN CONSTRUCTION ENTERPRISES (International Congress on Economics, Management and Business Studies, 2026)
Efficient utilization of resources is a key factor in enhancing the competitiveness and sustainability of construction enterprises. The construction industry is characterized by high material intensity, labor dependency, and capital investment, making resource management a critical aspect of economic performance. This study examines existing economic mechanisms for resource utilization in construction enterprises and proposes ways to improve them. The research highlights the importance of optimizing material, labor, and technical resources through modern management approaches, including digital technologies such as Building Information Modeling (BIM). The paper also analyzes challenges faced by construction firms and offers recommendations for increasing efficiency and reducing costs. The findings contribute to the development of more effective economic strategies in the construction sector.
Keywords: construction industry, resource efficiency, economic mechanisms, cost optimization, BIM, productivity